An attempt to identify factors influencing the effectiveness of physical exercise in virtual reality conditions in the treatment of anxiety and depressive disorders – study design - Pudlo, Robert; Kunert, Łukasz; Pankiewicz, Zbigniew; Szczegielniak, Anna Rebeka (Current Problems of Psychiatry, 2024)
Introduction: Virtual reality (VR) has been shown to have beneficial effects in the treatment of depressive disorders, anxiety disorders, eating disorders, and addictions. This method is relatively safe and noninvasive, but its effectiveness is variable, and predictors of effectiveness have been investigated in a limited manner. We hypothesized that personality traits could impact VR effectiveness, and that cognitive impairments might relate to its therapeutic success.Material and methods: The study involves a randomized sample of 40 patients diagnosed with anxiety and mood disorders (ICD-10 F3x and F4x) from a psychiatric rehabilitation daily unit. Over 12 weeks, they will participate in a therapeutic program that includes exercise sessions enhanced with virtual reality (VR) interventions lasting 10 to 12 minutes each. A control group of 40 patients will follow a standard therapeutic program without VR. During the screening phase, we will assess anxiety and depression severity using the HADS and STAI. We will also evaluate patients' physical fitness by using the 6MWT, personality traits by using the HEXACO-60 Personality Inventory, and cognitive functioning by the ACE III, MoCA, FAB and RAVL tests.Results: The procedure's effectiveness will be measured using HADS and STAI assessments for anxiety and depression at weeks 6, 12, and 4 weeks after the program.Conclusions: Defining the subpopulation of patients sensitive to the proposed therapeutic interventions and analyzing the factors influencing their treatment will allow offering therapy in virtual reality to those who will benefit the most from it.